Experimental and Numerical Study of the Effects Of Creating Openings in Existing RC Beams and StrengtheningWith CFRP - Hayder Qais Majeed (Engineering and Technology Journal, 2012)
This study presents an experimental and nonlinear finite element analysis of creating square openings in existing RC beams and strengthening with CFRP laminate. Flexural strengthening of reinforced concrete beams is now becoming more and more important in the field of structural maintenance and retrofitting. In the experimental programming, three RC beams were cast. Two beams were tested in the un-strengthened condition the first act as the solid Control beam, and the other have openings, the third one have opening and strengthening with CFRP laminate. The beams were also modeled using a FEM packaged (ANSYS 11). The results indicate that the strengthened beam recorded the highest failure load and its mode of failure was ductile. The numerical results seemed to be able to predict the behavior of the beams.